Exploring the Opportunities of Implementing Artificial Intelligence (AI) Technology for Teaching Arabic to Non-Native Speakers: A Theoretical Approach - H. L. M. Mohideen (RADINKA JAYA UTAMA PUBLISHER, 2024)
Language is a tool through which humans exchange their ideas and thoughts among themselves. It helps humans express their feelings and needs. Because of the global pervasion of Islam, the Arabic language unites Arabs and non-Arab Muslims under one religion. In Islamic perception, the Arabic language holds vital importance in Muslims' lives. Thus, Muslims consider learning and teaching Arabic in their day-to-day lives. Learning Arabic presents several challenges due to its complex grammar, diverse dialects, unfamiliar script, and significant differences from many other languages in terms of structure and vocabulary. These difficulties can make learning the language a demanding task for learners. This research aims to explore the importance of learning and teaching the Arabic language in the contemporary world, examine theoretical frameworks for incorporating AI in teaching Arabic to non-native speakers, and evaluate existing AI tools for it. The methodology adopted is qualitative. Primary and secondary data were collected. This research concludes that Arabic, as a language, is deeply intertwined with Islamic religious and cultural heritage, while also serving as a vital means of global communication. Teaching Arabic to non-native speakers poses unique challenges, but the implementing of AI technology offers promising solutions. AI enables personalized learning experiences, instant feedback, and diverse learning tools, ranging from text generation to virtual reality, enhancing language acquisition. By combining AI with traditional teaching methods, educators can address these challenges and maximize learning outcomes, ultimately shaping the future of Arabic language teaching to be more accessible, effective, and engaging worldwide.